Procedure to Ensure On-Time Delivery of Materials in Multifamily Housing Construction Projects Using Just-In-Time and Kitting In Small Construction - De la Cruz Valdivieso, Alfredo Félix (2025)
Construction companies are responsible for purchasing materials for the execution of construction projects, which consist of different stages; however, many times the materials do not arrive on time at the construction site. The material supply process is important within construction projects as it directly impacts the budget and schedule of the work. However, one of the most influential factors causing the delay in the delivery of material is the lack of a logistics plan for the supply of material in small companies. However, this leads to delays in the progress and delivery of the work. For this reason, this research focuses on ensuring the delivery time of construction materials in small construction companies for multi-family housing construction projects, specifically in the supply of materials through the use of the Just in Time and Kitting methodology, applying the use of an ERP. In this research, the following methodology is followed: (A) registration and analysis of information through expert judgment, (B) determination of the conventional material supply process in small construction companies, (C) development of the new supply process and (D) implementation of the new material supply process using the JIT and Kitting methodology. Finally, the result is a reduction in the delivery time of materials in the supply process, the metric being the average delivery time. In addition, a better management of the material supply process is obtained, in the logistics part. And the perception of the participants improved with the implementation of the new process. It is mainly concluded that the methodology used allows to ensure the delivery time of material, thus reducing the time in said process.